The influence of evaluation protocol on time spent exercising at a high level of oxygen uptake during continuous cycling - Merry, K. L.; Glaister, M.; Howatson, G.; Van Someren, K. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: This study evaluated the effects of protocol variation on the time spent exercising at =95% .VO2max during cycle ergometer trials performed at the exercise intensity associated with .VO2max (i .VO2max).